2008
DOI: 10.1073/pnas.0805022105
|View full text |Cite
|
Sign up to set email alerts
|

Brain potentials to native phoneme discrimination reveal the origin of individual differences in learning the sounds of a second language

Abstract: Human beings differ in their ability to master the sounds of their second language (L2). Phonetic training studies have proposed that differences in phonetic learning stem from differences in psychoacoustic abilities rather than speech-specific capabilities. We aimed at finding the origin of individual differences in L2 phonetic acquisition in natural learning contexts. We consider two alternative explanations: a general psychoacoustic origin vs. a speech-specific one. For this purpose, event-related potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
157
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(175 citation statements)
references
References 48 publications
16
157
2
Order By: Relevance
“…This may have to do with the fact that the magnitude of brain responses, i.e., ERPs to T5 rise time and MMN amplitude lack a speed component, and thus have less in common with one's efficiency of allocating attentional resources. The current findings of contribution of attention to speech processing are compatible with our previous study where visual attention switching could predict tone discrimination efficiency (Ou et al, 2015), as well as research that also found a role of attention in modulating perceptual sensitivity to speech sounds (e.g., Astheimer & Sanders, 2009;Díaz et al, 2008;Jesse & Janse, 2012). The significance of attention switching/ shifting in influencing the distinctiveness of speech representations has been hypothesized in the SAS hypothesis (Hari & Renvall, 2001;Lallier et al, 2010;Ruffino et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This may have to do with the fact that the magnitude of brain responses, i.e., ERPs to T5 rise time and MMN amplitude lack a speed component, and thus have less in common with one's efficiency of allocating attentional resources. The current findings of contribution of attention to speech processing are compatible with our previous study where visual attention switching could predict tone discrimination efficiency (Ou et al, 2015), as well as research that also found a role of attention in modulating perceptual sensitivity to speech sounds (e.g., Astheimer & Sanders, 2009;Díaz et al, 2008;Jesse & Janse, 2012). The significance of attention switching/ shifting in influencing the distinctiveness of speech representations has been hypothesized in the SAS hypothesis (Hari & Renvall, 2001;Lallier et al, 2010;Ruffino et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…Given that the size of MMN has been found to correlate with individual difference in auditory discrimination ability (e.g. Díaz, Baus, Escera, Costa, & Sebastián-Gallés, 2008;Jakoby, Goldstein, & Faust, 2011), the present findings suggest that auditory discrimination sensitivity, indexed by the MMN, was in general weaker in [-Per-Pro] compared with the other two groups, even to sound contrasts that they could distinguish with high accuracies behaviorally. Moreover, both the permutation and ANOVA tests confirmed the absence of P3a to T1/T2 in [-Per-Pro], whereas robust P3a components were observed in both [+Per+Pro] and [+Per-Pro].…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, auditory brainstem responses in language-impaired children suggest that low-level auditory processes contribute to the pathogenesis of language disorders (4). In adults, individual differences in perceptual abilities correlate with language-processing abilities in their native and a second language (5,6). The findings suggest a potential causal relationship between basic auditory processing ability and the efficiency of language learning in infancy and adulthood.…”
mentioning
confidence: 81%
“…For instance, Parbery-Clark et al (2009) found that the ability to perceive speech in background noise was positively correlated with auditory attention and working memory among individuals differing in musical training. The association of individual differences in speech perception and auditory attentional switching is also shown among L2 learners (Díaz et al, 2008). However, few investigations of individual differences in speech processing have been conducted with native speech perception among typically developed speakers.…”
mentioning
confidence: 99%
“…Apart from language disorders, much of the research in speech processing of typically developed speakers has characterized individual differences by employing participants differing in learning/training experience, including second language (L2) learning (Díaz, Baus, Escera, Costa, & Sebastián-Gallés, 2008;Lengeris & Hazan, 2010) and musical training (George & Coch, 2011;Parbery-Clark, Skoe, Lam, & Kraus, 2009) to assess its relationship with cognitive abilities. For instance, Parbery-Clark et al (2009) found that the ability to perceive speech in background noise was positively correlated with auditory attention and working memory among individuals differing in musical training.…”
mentioning
confidence: 99%